VILHELMAS ÞANAS BURKEVIÈIUS – THE BOOK WORKER - GAIDAMAVIČIŪTĖ, GERTRŪDA (Knygotyra, 2015)
Bibliophilia is the important part of the national culture, but the history of Lithuanian bibliophilia was not studied enough yet. In this work the activity of book collector Vilhelmas Žanas Burkevičius is examined. The tasks of this work is to analyse his works (also published or not). The analysis of activity of V. Ž. Burkevičius confirmes the supposition that the character of his activity reflects basic tendencies of the first half of XXth century bibliophilia. His work was influenced by complicated and contradictory conditions of Lithuanian political and cultural life. His bibliophilical interests reflected his proffesional and personal interests. V. Ž. Burkevičius harmonized his bibliophilical activity with the activity of book science: wrote some works on press, book culture and the history of bibliophilia. In his works he talked about the script in the times of the ban of the press, the history and organization of various libraries (public and personal), the history of Lithuanian bibliophilical society XXVII knygos mėgėjai. V. Ž. Burkevičius described the history and structure of his own personal library. He was also interested in the place of the book in modern society. V. Ž. Burkevičius considered that the book is going to die because of more improved information technologies (then it was radio). This sentence is often repeated and nowadays in due to television and computer technologies. Continuing this work is very important to make complete descriptions of the funds of private libraries, because only this can give the rich material for the history of the bibliophilia in Lithuania.